Pregnancy and Rheumatic Diseases - Hakan Terekeci; Cihan Top (Archives of Rheumatology, 2008)
Pregnancy is an issue that should be well discussed in all patients with rheumatic diseases in reproductive age groups. Pregnancies in women with rheumatic diseases require a multidisciplinary, carefully monitored, coordinated approach before, during and after pregnancy to ensure the best possible success for mother and baby. Infertility is rarely due to the disease but can be associated with cyclophosphamide therapy. Most rheumatic diseases that are well controlled prior to pregnancy do not deteriorate in pregnancy, providing that the patient continues with appropriate disease-modifying therapy. In contrast to systemic lupus erythematozus, antiphospholipid syndrome, vasculitis and systemic sclerosis there is little evidence for poor maternal or fetal outcomes in rheumatoid arthritis or other forms of inflammatory arthritis such as psoriasis and seronegative spondyloarthropathies. Some patients with inflammatory arthritis go in to remission during pregnancy. Patients with renal involvement may be at increased risk of disease flare. During pregnancy it is essential to monitor all aspects of disease activity such as renal involvement, as well as pregnancy complications such as intrauterine growth retardation, thrombo-embolic disease and preeclampsia, particularly in patients with systemic lupus erythematozus, antiphospholipid syndrome , vasculitis and systemic sclerosis. Post-partum flare is common in all the rheumatic diseases. (Romatizma 2008; 23: 143-50)